Research on the widths of protective coal pillars in main roadway based on the damaged foundation beam model - Yu, Xinglan; Feng, Tianxin; Cheng, Guoqiang (Frontiers in Earth Science, 2024)
The long-term stability of the protective coal pillar can ensure the normal and safe use of the roadway, and the integrity of the roadway plays an important role in the safe and efficient mining of coal mines. The initial damage and rheological damage caused by coal seam excavation disturbance have an important influence on the selection of a reasonable width of protective coal pillar. In this paper, based on the damage mechanics and the theory of elastic foundation beam, considering the influence of threshold and residual strength, a coupled damage constitutive relation of rock-like materials is proposed, and the mechanical model of elastic damage foundation beam is established. By solving the differential equation of the deflection curve of the beam, the influence range of the advance abutment pressure under the condition of coupling damage is obtained, and the width of the coal pillar is finally determined. The results show that compared with the elastic foundation beam model, after considering the coupling damage of coal, the influence range of advance abutment pressure increases with time in a certain time. After reaching a certain time, the influence range of the advance abutment pressure is almost no longer changed. In the case selected in this paper, the long-term stability of the roadway can be guaranteed when the width of the coal pillar is 120 m.